Nizar Qabbani and the Political Turmoil in the Middle East: A Critical Discourse Analysis of the Poem Hawāmisy alā Daftar al-Naksah - Nurwansyah, Agus (Contemporary Society and Politics Journal, 2024)
On June 5, 1967, Israel attacked and destroyed the air forces of Egypt, Syria, and Iraq, thereby crippling the Arab nations. This defeat is known as the Six-Day War or the June 1967 War. This loss also transformed Nizar Qabbani from a poet who wrote passionate love poems into a poet who wrote with a knife. This study uses a descriptive-qualitative method based on a critical paradigm. The analytical tool employed is Teun A. Van Dijk’s Critical Discourse Analysis from three dimensions: text, social cognition, and social context. This study reveals that the poem “Hawamisy ala Daftar al-Naksah” textually narrates the condition of the Arab nations post-Arab-Israeli War, where history had changed, and they had been defeated by Israel. In terms of social cognition, Nizar wrote the poem out of the grief experienced by his people. In terms of social context, the poem was written based on the reality of the Arab nations’ defeat by Israel, which brought shame, disappointment, and despair to them. Particularly, it addresses the 50,000 new refugees, the leaders who could only engage in rhetoric, and the silencing of voices through his poems.